The Suicide and Homicide Risk Assessment and Prevention Treatment Planner, with DSM-5 Updates. - Jongsma, Arthur E. (Practice planners., 2015)
This timesaving resource features: -Treatment plan components for 27 behaviorally based presenting problems -Over 1,000 prewritten treatment goals, objectives, and interventions-plus space to record your own treatment plan options -A step-by-step guide to writing treatment plans that meet the requirements of most insurance companies and third-party payors The Suicide and Homicide Risk Assessment & Prevention Treatment Planner provides all the elements necessary to quickly and easily develop formal treatment plans that satisfy the demands of HMOs, managed care companies, third-party payors, and state and federal review agencies.-A critical tool for assessing suicidal and homicidal risks in a wide range of treatment populations -Saves you hours of time-consuming paperwork, yet offers the freedom to develop customized treatment plans for your adult, adolescent, and child clients -Organized around 27 main presenting problems and covering all client populations (suicidal adults, adolescents, and children) as well as homicidal personality types and risk factors including antisocial, psychotic, PTSD, and manipulative -Over 1,000 well-crafted, clear statements describe the behavioral manifestations of each relational problem, long-term goals, short-term objectives, and clinically tested treatment options -Easy-to-use reference format helps locate treatment plan components by behavioral problem -Includes a sample treatment plan that conforms to the requirements of most third-party payors and accrediting agencies (including HCFA, JCAHO, and NCQA).